De la difficulté de concilier lutte noire pour l’égalité et aspirations olympiques : Lee Evans et les Jeux de Mexico (1968) - François-René Julliard (Cahiers d’histoire.)
This article retraces the apprenticeship and militant itinerary of former Olympic champion and 400-meter world record-holder Lee Evans, over a brief but important period for him, culminating in the Mexico Games (1968). Evans was one of the athletes involved in the mobilization of black student-athletes at San Jose State College, before advocating a black boycott of the Games. For him, these commitments were not without their own inner contradictions, which culminated in Mexico City. The day after Tommie Smith and John Carlos famously raised their fists on the 200-meter podium, Evans, winner of the 400-meter race, briefly wore a Black Panther beret and raised his fist on the podium before the U.S. anthem rang out. At the time, however, he refused to accept the political dimension of his gesture.